Exergaming and Treadmill Training in Stroke Patients - Tanveer, Fahad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Treadmill training is nowadays considered more efficient in improving balance and mobility rather than simply walking on an even surface. In patients with chronic stroke, changes in cortico-motor excitability are induced to improve balance and gait performance. There is simple treadmill training that can enhance and motivate patients to walk but treadmill training with body support is safer and more comfortable for patients. In one study the effect of treadmill therapy with the optic flow on balance control and gait training helps the patients of stroke in regaining functional independence in the community. Outcome measures were used that were Time Up and Go test, Functional Reach Test (FRT), 10-minute walk test, and 6- minute walk test. It proved a better result for patients with chronic stroke [1]. Apart from gait training, treadmill training may be able to help in balance dysfunction in most individuals who have to complain of stroke [2]. It enhances the balance and mobility skills of chronic stroke patients. Treadmill training motivates the subject to give better physical performance after stroke. Exercise video games are an innovative idea not commonly used in Pakistan for stroke rehabilitation. Both these techniques are used to enhance motivation and self-confidence in walking and maintaining balance. It keeps the subject engaged in physical therapy sessions for a long time after stroke. Thus, video games and treadmill training are used in various clinical settings for stroke rehabilitation. A combination of both these techniques would help decrease balance and mobility impairments through effective use of Exergaming and Treadmill training in patients suffering from a stroke in the chronic phase. This study would help the therapists across the locality to enlist a better management approach to treat subjects with chronic stroke.